2004
DOI: 10.1128/jvi.78.20.10911-10919.2004
|View full text |Cite
|
Sign up to set email alerts
|

Splice Junction Map of Simian Parvovirus Transcripts

Abstract: The transcription map of simian parvovirus (SPV), an Erythrovirus similar to Parvovirus B19, was investigated. RNA was extracted from tissues of experimentally infected cynomolgus macaques and subjected to reverse transcription-PCR with SPV-specific primers. The PCR products were cloned and sequenced to identify splice junctions. A total of 14 distinct sequences were identified as putative partial transcripts. Of these, 13 were spliced; a single unspliced transcript putatively encoded NS1. Sequence analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Surprisingly, RNase protection assays could not detect RNAs initiated at the previously identified P36 promoter, following productive AMDV-G infections of CRFK cells at either 37°C or 32°C or following plasmid transfection. Thus, the expression profile of AMDV-G is similar to that of the erythroviruses B19 (24) and simian parvovirus (20,40), which also generate genetic diversity by alternative splicing and polyadenylation of a single pre-mRNA generated from a promoter at the left end of the genome.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Surprisingly, RNase protection assays could not detect RNAs initiated at the previously identified P36 promoter, following productive AMDV-G infections of CRFK cells at either 37°C or 32°C or following plasmid transfection. Thus, the expression profile of AMDV-G is similar to that of the erythroviruses B19 (24) and simian parvovirus (20,40), which also generate genetic diversity by alternative splicing and polyadenylation of a single pre-mRNA generated from a promoter at the left end of the genome.…”
Section: Discussionmentioning
confidence: 81%
“…This is often accomplished by transactivation of the capsid gene promoter. In productive AMDV infection of CRFK cells, however, as is also the case for B19 (24) and SPV (20,40), individual mRNAs are generated posttranscriptionally from a single pre-mRNA by a combination of alternative polyadenylation and alternative splicing. There is no evidence that processing of P3-generated pre-mRNAs changes during the course of infection (J. Qiu and D. Pintel, unpublished data), and thus all AMDV RNAs generated during infection increase coordinately with replicating DNA and in concert with increased virus and capsid protein production.…”
Section: Discussionmentioning
confidence: 96%
“…Similar to the organization of B19, SPV has two large open reading frames (ORFs) in either half of the genome. The left ORF encodes the nonstructural NS1 protein, and the right ORF encodes the two capsid proteins VP1 and VP2 (3,31). Expression of the VP2 ORF of SPV results in the generation of virus-like particles and has been useful as a diagnostic reagent for SPV antibody detection (4).…”
mentioning
confidence: 99%
“…The splice junctions of SPV RNA isolated from the liver of SPV-infected monkey fetuses have been determined by reverse transcription-PCR (RT-PCR) and Northern blot analysis (31). In this report, we present a detailed characterization of the transcription and protein expression profile of SPV RNA generated following transfection of monkey COS cells.…”
mentioning
confidence: 99%
“…Strain AMDV-G is a variant of strain Utah 1, which was adapted to grow permissively in Crandell feline kidney cells (CrFK) at 32°C and is nonpathogenic in adult mink (8). It has been demonstrated that AMDV-G, similar to human parvoviruses in the genus of Erythrovirus (20,22,33), uses a single promoter at the left-hand end of the genome (24). This promoter encodes a pre-mRNA that is processed by alternative splicing and alternative polyadenylation to generate six mRNAs (24) (Fig.…”
mentioning
confidence: 99%